Analisis Perkembangan Local Wisdom Di Bumi Nusantara Pada Era Disrupsi Tekhnologi - Jannah, Nur; Halim Soebahar; Moch. Chotib; Muhammad Noor Harisudin; Stephen Amukune (Al Qodiri : Jurnal Pendidikan, Sosial dan Keagamaan, 2025)
The development of digital technology has significantly changed the way the people of the archipelago preserve local wisdom. As a cultural heritage that reflects traditional values, local wisdom now faces challenges from the dominance of global culture, homogenization of values, and decreased involvement of the younger generation. On the other hand, digital technology offers opportunities as a tool for documentation, promotion, and preservation of local culture through platforms such as digital applications and social media. This study aims to analyze the opportunities and challenges faced by digitalization in preserving local wisdom in Indonesia. With a qualitative approach based on library research, data were obtained from relevant literature, such as books, journals, and official documents. The research findings show that digital technology can document and promote local wisdom through social media, applications, and video platforms. However, serious challenges arise from the risk of cultural commodification and inequality of access to technology in remote areas. Therefore, synergy between traditional methods and digital technology is very important to maintain the sustainability and authenticity of local wisdom amidst the flow of globalization. Keywords: local wisdom; digitalization; local wisdom; cultural preservation; digital era.